Analysis of the humoral immune response to chlamydial genital infection in guinea pigs. - Batteiger, B E (1987)
Studies using the guinea pig model of chlamydial genital infection with the Chlamydia psittaci agent of guinea pig inclusion conjunctivitis (GPIC) have shown that serum and local antibodies play a role both in the resolution of infection and in protection against reinfection. Thus, this model is suited for further exploration of immune mechanisms and for vaccine studies with chlamydial macromolecules. We have further characterized the model by assessing the antigen-specific antibody response to experimental genital infection by using immunoblotting to assay both genital secretions and serum. The GPIC agent was characterized by analysis of outer membrane proteins, which indicated that the GPIC agent possessed a major outer membrane protein (MOMP), with a molecular mass of 39 kilodaltons (kDa), and a 61-kDa protein, analogous to cysteine-rich 60-kDa proteins or doublets of Chlamydia trachomatis strains. As indicated by immunoblotting, most infected animals produced serum immunoglobulin G antibodies to MOMP, the 61-kDa proteins, an 84-kDa outer membrane protein, and lipopolysaccharide. Such serum antibodies persisted for at least 813 days after primary genital infection. Immunoglobulin A antibodies against the 61-kDa proteins, lipopolysaccharide, and MOMP, but not the 84-kDa protein, were detected in secretions. Animals challenged with GPIC 825 days after primary infection became infected again despite the presence of serum antibodies, but the period of chlamydial shedding was significantly shorter and less intense than in primary infections. Although the specific mechanism is not known, these data suggest that a long-lasting immune effect is capable of altering the course of infection late after primary infection. Correlation of the antigen-specific antibody response and other immune parameters with the duration and degree of protective immunity induced by infection or vaccination may be helpful in further understanding the nature of such protective immunity.